Phase specific comparisons of high and low vertical jump performance in collegiate female athletes - Donahue, P. T.; Rush, M.; McInnis, A. K.; Littlefield, T. (Journal of Science in Sport and Exercise, 2023)
Introduction Countermovement vertical jump testing has become a staple in athlete assessment protocols. As the popularity of jump testing has grown, a need and interest has also grown in identifying the factors that underpin high-level outputs. As jump height alone as a variable in evaluating vertical jump performance has been questioned in athletic populations, other variables such as the reactive strength index modified (RSIm) allow for not only evaluating the outcome, but the strategy used in obtaining that outcome.